Quels espaces scolaires pour le bien-être relationnel ? Enquête sur le ressenti des collégiens français - Thibaut Hébert; Éric Dugas (Éducation et Socialisation)
The purpose of this enquiry carried out in different secondary schools is to observe which areas of the school are seen by pupils to be safest and least safe. In other words, what spatial modifications could be thought out in order to guarantee a feeling of security and pupils’ well-being. The results show that spaces which are not under surveillance are seen as risky by secondary school children (n =544). Among younger pupils, the playground causes most anxiety, whereas the older children feel at risk just outside the school gates. Within the group of younger pupils, the boys feel unsafe in the toilets whereas the girls see the stairs as a risky place. In the older group, the boys feel more fear in the sports changing rooms. The trends revealed in this article call for thought about the different areas within schools in view of the new pedagogical perspectives and the well being of those using the schools.